2015
DOI: 10.1007/s13593-015-0310-5
|View full text |Cite
|
Sign up to set email alerts
|

Transplastomic plants for innovations in agriculture. A review

Abstract: Food production has to be significantly increased in order to feed the fast growing global population estimated to be 9.1 billion by 2050. The Green Revolution and the development of advanced plant breeding tools have led to a significant increase in agricultural production since the 1960s. However, hundreds of millions of humans are still undernourished, while the area of total arable land is close to its maximum utilization and may even decrease due to climate change, urbanization, and pollution. All these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 370 publications
(407 reference statements)
0
27
0
1
Order By: Relevance
“…The response of different genotypes of the same crop species to drought or heat periods may vary in wide range (Vassileva et al, 2009(Vassileva et al, , 2011(Vassileva et al, , 2012Erice et al, 2010Erice et al, , 2011Yin et al, 2010 ;Parry et al, 2011;Prior et al, 2011;Cao et al, 2014 ;Habash et al, 2014;Topbjerg et al, 2014;Acuna-Galinda et al, 2015 ;Lopes et al, 2015;Wani et al, 2015;Wehner et al, 2015). This is the basis for breeding of crop varieties with a better performance under abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…The response of different genotypes of the same crop species to drought or heat periods may vary in wide range (Vassileva et al, 2009(Vassileva et al, , 2011(Vassileva et al, , 2012Erice et al, 2010Erice et al, , 2011Yin et al, 2010 ;Parry et al, 2011;Prior et al, 2011;Cao et al, 2014 ;Habash et al, 2014;Topbjerg et al, 2014;Acuna-Galinda et al, 2015 ;Lopes et al, 2015;Wani et al, 2015;Wehner et al, 2015). This is the basis for breeding of crop varieties with a better performance under abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…However, more than half of wheat plantation is in Zn-deficient soils and the Zn concentration in wheat grain is generally too low to supply sufficient Zn nutrition for human health (Alloway 2008;Cakmak 2008). Therefore, more attention has been paid to the improvement of human Zn intake by biofortification of wheat grain with Zn (Schroeder et al 2013;Wheeler and von Braun 2013;Myers et al 2014;Wani et al 2015). The genetic biofortification via breeding Zn-enriched wheat varieties represents a long-term strategy with important advantages.…”
Section: Introductionmentioning
confidence: 99%
“…The fusion protein approach indicates a way to avoid unbalanced immune responses continuously reported for tetravalent formulations consisting of stoichiometrically mixed monovalent vaccines (Capeding et al 2014;Hadinegoro et al 2015;Villar et al 2015). Furthermore, the transformation of the plastid genome represents a promising possibility for the high-level, cost-effective, clean and safe expression of therapeutically relevant proteins in commercial applications (Wani et al 2015). A theoretical technoeconomic case study showed that plants can be highly competitive production platforms for biopharmaceuticals (Tuse et al 2014).…”
Section: Discussionmentioning
confidence: 99%